JNK regulation of nerve cell calcium : a possible mechanism in psychiatric disease - Helminen, Hanna (My University, 2019)
Psychiatric disorders are a big problem in the modern world. The symptoms of these diseases vary, but common for all of them is that they are overpowering, consistent, and hamper daily life. Even though many treatments are developed, many patients do not get effective treatment for their condition. Therefore, new studies are needed to better understand the molecular mechanisms leading to mental abnormalities and in this way, recognize new action mechanisms for antidepressant drugs. The aim of this project was to study how a pharmacological inhibition of c-Jun N-terminal kinase (JNK) in neurons affects their calcium signaling. To enable the research of calcium signaling, the neurons were transfected with genetically encoded calcium indicators. To monitor the calcium indicators, the neurons were studied with live cell imaging using a widefield fluorescence microscope. Calcium influx into neurons was stimulated with two different stimulation mediums (30 mM potassium chloride or 5 µM ionomycin in imaging medium). After imaging, image and statistical analyses were performed. Results suggest that inhibition of JNK potentiates cytosolic calcium levels and enables faster calcium level recovery in the endoplasmic reticulum. According to earlier results, the inhibition of JNK may contribute to an improved mood. The results of this thesis raise calcium homeostasis regulation as a possible underlying mechanism. However, the role of JNK inhibition in mental disorders needs to be further studied.
Keywords: calcium signaling, c-Jun N-terminal kinase (JNK), fluorescence microscopy, genetically-encoded Ca2+ indicators, live cell imaging, mental disorders, neurons